In situ Root Phenotypes of Cotton Seedlings Under Phosphorus Stress Revealed Through RhizoPot - Zhang, Zichen; Zhu, Lingxiao; Li, Dongxiao; Wang, Nan; Sun, Hongchun; Zhang, Yongjiang; Zhang, Ke; Li, Anchang; Bai, Zhiying; Li, Cundong; Liu, Liantao (Frontiers in Plant Science, 2021)
Phosphorus (P) deficiency is a common challenge in crop production because of its poor mobility through the soil. The root system plays a significant role in P absorption from the soil and is the initial indicator of low phosphorus. However, the phenotypic dynamics and longevity of cotton roots under phosphorus stress are still unknown. In this study, RhizoPot, an improvised in situ root observation device, was used to monitor the dynamics of root phenotypes of cotton seedlings under P-deficient (PD) and P-replete (PR) conditions. Low phosphorus stress reduced P absorption and accumulation in the roots, leading to low dry matter accumulation. Cotton seedlings responded to low P stress by increasing the number of lateral roots, specific root length, branch density, and root length density. Besides, the length of root hairs increased, and the lifespan of root hairs was prolonged. Low phosphorus stress also reduced the average diameter of roots, promoted root extension, expanded the root coverage area, and increased the range of phosphorus acquisition. Principal component analysis (PCA) revealed that the net root growth rate, root length density, root dry weight, phosphorus absorption efficiency, average root hair length, and taproot daily growth significantly influence cotton root architecture. Collectively, these results show that low phosphorus stress reduces the net growth rate of cotton seedling roots and restricts plant growth. Plants respond to phosphorus deficiency by extending the lifespan of root hairs and increasing specific root length and lateral root branch density. This change in root system architecture improves the adaptability of plants to low-phosphorus stress. The findings of this study may guide the selection of cotton varieties with efficient phosphorus utilization.